Gold Nanocage-Incorporated Poly(ε-Caprolactone) (PCL) Fibers for Chemophotothermal Synergistic Cancer Therapy - Ju Hyang Park; Hojun Seo; Da In Kim; Ji Hyun Choi; Jin Ho Son; Jongbok Kim; Geon Dae Moon; Dong Choon Hyun (MDPI AG, 2019)
This paper introduces a new fibrous system for synergistic cancer therapy, which consists of gold nanocage (AuNC)-loaded poly(ε-caprolactone) (PCL) fibers with encapsulation of a chemotherapeutic anticancer drug in their core and loading of a phase-changeable fatty acid in their sheath. Under on⁻off switching of near-infrared (NIR) light irradiation, the excellent photothermal ability and photostability of AuNCs allows repeated, significant heating of the fibers to a temperature available to hyperthermia. Simultaneously, the NIR light-induced heat generation enables the melting out of the loaded fatty acid, leading to a rapid release of the drug molecules from the fibers. The combination of this NIR light-triggered drug release with the repeated hyperthermia treatment exhibits excellent anticancer efficacy.